THE IMPACT OF CULTURE ENVIRONTMENT TO HUMAN RESOURCES MANAGEMENT IMPLEMENTATION IN SEPODO TOBACCO SHOP - Masykuri, Alfan Taufiq; Sasana, Hadi (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2023)
There are many Micro Small and Medium Enterprises (MSMEs) that appears in Indonesia. This was related with new adaptation concept that adopted to Micro Small and Medium Enterprises (MSMEs) that different concept with big company. This research purposes to describe about how the management concept adapted and implemented in Micro, Small, and Medium Enterprises (MSMEs) of Tembakau Sepodo Sole Proprietorship. In every business must be need and use human resources management concept. The one that make different of management in many places is how to communicate to implement the concept theory in to their business as suitable as their place and culture. This research uses empirical-explorative approach and analyzed by comparative study with theory that was created and published before. This study was trying to observe, induction, conduction, and evaluation. This was need 25 days to observe the operational process in Tembakau Sepodo Sole Proprietorship so it can be described from Human Resources Management point of view. How the job was plotted not only in the formal communication. It needs more awareness in self position, age, and experience. It’s about social culture there.